Consumer Protection Against Inconsistencies in Nutrition Facts Information on Whey Protein Milk Product Labels (Legal Analysis Study) - Nurrahman, Rian Alfi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Trade arises due to several background reasons, namely philosophical, legal and sociological backgrounds that greatly influence the development and regulation of the process of running a trade. This study aims to analyze the implementation of labeling in whey protein milk products in Indonesia and product responsibility for business actors for inapropriate nutritional value information. The method used in this thesis research is a doctrinal/normative aproach. The specification of this research uses analytical evaluative. The type of research used in this research is normative juridical, namely library legal research conducted by examining library materials or secondary data. Data analysis in this research is an interactive analysis model according to Miles and Huberman. Conclusion and suggestions, The laws and regulations implemented in Indonesia have considered the rights and obligations of business actors and the public as consumers, although there is no guarantee that all producers have good intentions. Business actors are expected to implement quality control on all products produced and marketed by referring to the references set by the government. On the part of the wider community as consumers, there needs to be caution in consuming the results of a product, one of which is by observing what is stated on the label to ensure the method and use according to needs.